2016
DOI: 10.1155/2016/5029797
|View full text |Cite
|
Sign up to set email alerts
|

7,8-DHF Treatment Induces Cyr61 Expression to Suppress Hypoxia Induced ER Stress in HK-2 Cells

Abstract: Acute kidney injury (AKI) is a common syndrome which is strongly linked to high morbidity and mortality. Hypoxia is the leading cause of AKI and the proximal renal tubular cells are the most damaged part in the kidney during this period. It has been observed that 7,8-dihydroxyflavone (7,8-DHF) plays a protective role by acting on antiapoptosis and antioxidative stress. In this study we explored functions of 7,8-DHF in protecting human proximal tubular cell line HK-2 from hypoxia insults. We observed that treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
(42 reference statements)
4
6
0
Order By: Relevance
“…In tubulointerstitium, there were 480 DEGs between IgA nephropathy and healthy control. [43,44]. Therefore, our results of WGCNA and Gene ontology enrichment analysis were consistent with previous studies results, at least in part, Cyr61 as a matrix molecule related to apoptosis although the underlying mechanisms of proteinuria in IgA nephropathy still need to be explored.…”
Section: Discussionsupporting
confidence: 91%
“…In tubulointerstitium, there were 480 DEGs between IgA nephropathy and healthy control. [43,44]. Therefore, our results of WGCNA and Gene ontology enrichment analysis were consistent with previous studies results, at least in part, Cyr61 as a matrix molecule related to apoptosis although the underlying mechanisms of proteinuria in IgA nephropathy still need to be explored.…”
Section: Discussionsupporting
confidence: 91%
“…Micropropagation has been used to generate Chinese yam microtubers in tissue culture, which are useful to avoid the carryover of viruses during long-term vegetative propagation (Nagasawa and Finer 1989 ; Kohmura et al 1995 ; Kadota and Niimi 2004 ; Li et al 2014 ). Reference genes suitable for quantitative expression analysis have also been identified to enable further molecular studies (Zhao et al 2016 ).…”
Section: Current Research Status and Breeding Objectivesmentioning
confidence: 99%
“…The encoded protein interacts with several integrins and with heparan sulfate proteoglycan 23 . This protein also plays a role in cell proliferation, differentiation, angiogenesis, apoptosis, and extracellular matrix formation 24, 25 . Previous study found that CYR61 had an anti-apoptotic effect on cardiac myocytes under oxidative stress and a proangiogenic property 26 .…”
Section: Discussionmentioning
confidence: 99%